Comparative Analysis of Background Subtraction, Haar Cascade and SSD Methods in Detecting Cars - Tanaya, Tristan Nugraha; Putra, I Gusti Ngurah Anom Cahyadi (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
This research was conducted to detect and count cars that are passing on the highway quickly. In this study, 3 methods will be applied, namely the Background Subtraction, Haar Cascade, and Single Shot Detector (SSD) methods. This study will compare the best methods for calculating cars on the highway. Based on the results of research using the Haar Cascade method, the results are quite good compared to other methods. But using these three methods the author has not gotten satisfactory results. Due to many factors that cause this comparison is not satisfactory. Starting with simple coding, poor video quality is also one of the factors that this research is unsatisfactory .